The Influence of Online Games on English Language Development Among High School Students: A Qualitative Study: English - R. Rabdillah Oktariangga Raja hasril; Nur Wahidah Thayib Pido (English Education Department, 2026)
This qualitative study examines the influence of online games on English language development among high school students in Pekan baru, Riau Province, Indonesia. Despite growing scholarly interest in digital game-based language learning (DGBLL), empirical qualitative evidence from Indonesian secondary school contexts remains scarce. Employing a qualitative research design, data were collected from n = 20 students (Grades 10–12, aged 15–18) through in-depth interviews, participant observation, and open-ended questionnaires over an eight-week period. Data were analysed using thematic analysis following Braun and Clarke's (2006) six-phase framework. Findings reveal four overarching themes: (1) vocabulary acquisition through contextualised in-game exposure; (2) enhancement of listening and speaking skills via real-time multiplayer communication; (3) reduction of foreign language anxiety (FLA) in informal gaming environments; and (4) challenges pertaining to inappropriate linguistic register and the absence of pedagogical scaffolding. The study concludes that online games function as effective supplementary tools for English language development when purposefully integrated into a structured pedagogical framework. Implications for EFL curriculum design and teacher professional development in Indonesian secondary schools are discussed.